Analysis of electron emission characteristics of triggered vacuum switch based on cold cathode materials - Jilu Xia; Shifei Liu; Yijie Sun; Peng Fan; Zicheng Zhang (AIP Advances, 2022)
A trigger vacuum switch that works for a long time is subject to the stable emission of initial electrons. Cold cathode materials such as velvet and carbon fiber have the characteristics of large emission electron area, uniformity, and stability. In this paper, two cold cathode materials, namely T4 rayon velvet and T300 carbon fiber board, are attached. They were used on the surface of the vacuum switch cathode, the trigger electrode was located in the middle of the cathode, and the trigger vacuum switch was triggered by a positive polarity high-voltage pulse along the surface flashover. The breakdown voltage and dispersion were studied in the form of capacitive discharge, and the electron emission characteristics of the two materials were explored from a microscopic perspective, such as through scanning electron microscope and energy dispersive spectrometer element analysis. The results show that the triggering vacuum switch using this cold cathode material has stable triggering, wide operating voltage, and low breakdown voltage dispersion. The electron emission of the velvet has both fiber tip emission and lateral flashover mechanism, and carbon fiber is prone to surface damage; the anode metal surface is partially carbonized due to electron sputtering.